Evaluation of the Effect of Platelet Rich Plasma and Injectable Platelet Rich Fibrin on the formation of gingival invagination (Journal of Hama University, 2022)
This clinical trial aimed to compare the potential effect of platelet rich plasma (PRP) and injectable platelet rich fibrin(I-PRF) on gingival invagination formation60 patients who required fixed orthodontic treatment and maxillary first premolar extractions participated in this trial , they were divided into three different groups:The control group: 20 patients (12 females, 8 males; mean age, 20.6±2.1 years) didn’t receive any injectionsThe PRP group: 20 patients ( 10 females, 10 males; mean age, 20.9±2.3 years) received PRP injectionsThe I-PRF group: 20 patients (14 females, 6 male; mean age, 21.8±1.8 years) received I-prf injectionsPRP and I-PRF injections were done around the upper canines. 0,8 weeks after the start of the retraction.incidence ( Presence/absence ) and severity of gingival invaginations were recorded in each groupGingival invaginations developed more frequently in the control group ( 80%) than the PRP group (55% ) and I-PRF group (45%).severity of gingival invaginations was lower in the experimental groups with a statistically significant difference. Gingival invaginations development is a frequent finding during orthodontic space closure and Local injection of PRP and I-PRF in the present study resulted in reducing its incidence and severity